Prostate Cancer Screening in Middle-Aged and Older American Men: Combined Effects of Ethnicity and Years of Schooling - Shervin Assari (Baqiyatallah University of Medical Sciences, 2020)
Background: Prostate cancer screening is more commonly utilized by highly educated people. As shown by marginalization-related diminished returns (MDRs), the effects of socioeconomic status (SES) such as education on the health outcomes are considerably smaller for ethnic minorities than for Whites. The role of MDRs as a source of ethnic health disparities is, however, still unknown. Objectives: The current study had two aims: first, to explore the association between years of schooling and having taken a prostate-specific antigen (PSA) test among men in the US, and second, to explore ethnic differences in this association. Methods: This study was a secondary analysis of data from the National Health Interview Survey (NHIS-2015). The data of 5,053 men aged 55 years or older who were either Latino, non-Latino, African-American, or White were analyzed. Years of schooling was the independent variable. The dependent variable was taking a PSA test sometime during one's lifetime. Age, region, and employment were the control variables. Ethnicity was the focal moderating variable. Binary logistic regression was used for data analysis. Results: A higher number of years of schooling was associated with higher odds of having taken a PSA test, net of all confounders. Ethnicity showed a significant statistical interaction with years of schooling on having taken a PSA test. This interaction was suggestive of a smaller slope for Latino men than non-Latino men. White and African American men did not show differential effects of years of schooling on having taken a PSA test. Conclusion: Similar to the MDRs patterns in other domains, non-Latino White men show more health gain from their years of schooling than Latino men. Highly educated Latino men still need programs to encourage their use of prostate cancer screening.